DEVELOPING INTERACTIVE PLATFORMS FOR TEACHING DESCRIPTIVE GEOMETRY IN DISTANCE LEARNING: ENHANCING ENGAGEMENT AND LEARNING OUTCOMES - Yuldashev Salmonxon Iqboljon ugli (Bright Mind Publishing, 2025)
The shift toward distance learning in higher education necessitates innovative strategies for teaching traditionally hands-on disciplines such as Descriptive Geometry. Digital platforms provide interactive, immersive, and collaborative environments that can replicate and enhance classroom experiences, enabling students to develop spatial reasoning, geometric visualization, and problem-solving skills remotely. This paper examines the design, implementation, and effectiveness of interactive platforms for teaching Descriptive Geometry in distance learning contexts. Structured according to the IMRaD framework, the research combines literature review, platform development case studies, and experimental evaluation in higher education settings. Results indicate that interactive platforms incorporating 3D modeling tools, virtual laboratories, real-time feedback, and gamified learning significantly improve comprehension, engagement, and student satisfaction. The discussion addresses pedagogical design principles, technological challenges, and strategies to optimize interactivity and learning outcomes. The conclusion emphasizes that creating well-designed interactive platforms is essential for modernizing Descriptive Geometry instruction in distance education, fostering digital literacy, and preparing students for professional and technological demands.
Keywords: Descriptive Geometry, Distance Learning, Interactive Platforms, Virtual Laboratories, 3D Modeling, Online Education, Gamification, Spatial Visualization.